Graph interpretation for the Applied Knowledge Test - Jones, N; Fisher, R (SAGE Publications, 2019)
Systematic reviews and meta-analyses can help busy clinicians to evaluate and interpret large volumes of information drawn together from individual trials. They are placed at the summit of the hierarchy of research design, in part because of the precision and power that they provide. Understanding and interpreting the results of a systematic review or meta-analysis are therefore essential skills for any practicing clinician. In this article, we will review three of the common types of figure you may be presented with in a systematic review, a meta-analysis or in your Applied Knowledge Test. Caution - all three use fictional data!